Modern Techniques for Nano- and Microreactors/-reactions - Caruso, Frank.; Caruso, Frank. (Advances in Polymer Science,, 2010)
-Encapsulation by Miniemulsion Polymerization By K. Landfester and C. K. Weiss -Enzyme-Encapsulated Layer-by-Layer Assemblies: Current Status and Challenges Toward Ultimate Nanodevices By K. Ariga, Q. Ji, and J. P. Hill -Non-LBL Assembly and Encapsulation Uses 1 of Nanoparticle-Shelled Hollow Spheres 2 By G.C. Kini, S. L. Biswal, and M. S. Wong -Polymersomes: A Synthetic Biological Approach to Encapsulation and Delivery By M. Massignani, H. Lomas, and G. Battaglia -Reaction Vessels Assembled by the Sequential Adsorption of Polymers By A.D. Price, A.P.R. Johnston, G.K. Such, and F. Caruso.